Strategi Negosiasi Efektif di Era Digital melalui Platform Digital - Dinda Rizqia Maulana; Annabilla Zahra; Khairatun Hisan; Lilik Sumarni (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The digital age has revolutionized many aspects of life, including the way we negotiate. Digital platforms such as social media, email and video conferencing have opened up new opportunities to negotiate with parties around the world. However, these changes also present new challenges that require adaptive and innovative negotiation strategies. This research aims to observe and understand the interactions and dynamics of negotiations taking place on digital platforms. Qualitative methods were used to analyze effective negotiation strategies in the digital era through various digital platforms. Data was collected through in-depth interviews with digital platform users, direct observation of the negotiation process on digital platforms, as well as a literacy review of previous research. The results show that negotiations are increasingly turning to online platforms that offer flexibility, wide coverage and easy access to information. However, digital negotiations also face significant challenges such as a lack of non-verbal communication, difficulty in building trust, and potential technological disruptions. To create effective negotiations in the digital age, an adaptive strategy is needed that takes into account the unique characteristics of digital negotiations and helps companies reach mutually beneficial agreements. This strategy includes seven steps outlined by Poerwanto (2014), namely preparation, first contact, assessment, confrontation, conciliation, solution, and post-negotiation.